Atlas Hypoplasia and Ossification of the Transverse Atlantal Ligament: A Rare Cause of Cervical Myelopathy. (5th December 2012) - Bokhari, Rakan; Baeesa, Saleh
Abstract : Myelopathy at the level of the atlas is rarely encountered by the practicing spine surgeon. Due to the region's unique anatomy, compression of the cord at this level is either caused by a large compressing lesion or an abnormally stenotic canal. We describe a rare instance of a congenitally stenotic canal due to a hypoplastic intact posterior arch of atlas, coexisting with an extremely rare ossified transverse ligament of the atlas. The coexistence of these two lesions has only been documented thrice before. We describe the clinical presentation, imaging findings, and favorable response to surgery.